2014
DOI: 10.1002/2013jd021431
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of water vapor budget and its future change in the Yellow-Huai-Hai region of China

Abstract: This study aims to analyze the atmospheric water vapor budget changes in the Yellow-Huai-Hai River basin and explore the possible relationship between water vapor budget and precipitation. The Fifth Phase of the Coupled Model Intercomparison Project is used to assess the future change of water vapor in the region. Corrected general circulation model outputs are evaluated, and multimodel ensemble is used to project the future atmospheric water vapor changes. Results show the following: (1) Water vapor in wet su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…The data sources include monthly mean temperature and monthly precipitation data from more than 2400 well-distributed climate stations across China, as well as digital elevation model (DEM) data. The meteorological gridded data sets were generated by CMDSSS through the thin plate spline (TPS) method using ANUSPLIN software (ERSI, Redlands, California, USA), and a goodness of fit of the interpolated values was validated by CMDSSS (Shi et al, 2014). The growing season temperature (GST) and growing season precipitation (GSP) were defined as the average air temperature and the accumulated precipitation during the growing season of alpine grasslands from May to September.…”
Section: Climate Datamentioning
confidence: 99%
“…The data sources include monthly mean temperature and monthly precipitation data from more than 2400 well-distributed climate stations across China, as well as digital elevation model (DEM) data. The meteorological gridded data sets were generated by CMDSSS through the thin plate spline (TPS) method using ANUSPLIN software (ERSI, Redlands, California, USA), and a goodness of fit of the interpolated values was validated by CMDSSS (Shi et al, 2014). The growing season temperature (GST) and growing season precipitation (GSP) were defined as the average air temperature and the accumulated precipitation during the growing season of alpine grasslands from May to September.…”
Section: Climate Datamentioning
confidence: 99%
“…Water vapour transport budget is the balance between the inputs and outputs of moisture over a region in a specific time period, which reflects the amount of the regional atmospheric water vapour falling to the ground and greatly impacts regional precipitation (Shi et al, ). Inter‐annual changes of the water vapour budget will definitely have important effects on the regional precipitation.…”
Section: Resultsmentioning
confidence: 99%
“…Yan et al (2014) analyzed the daily precipitation and showed that the precipitation of most months in drought years was reduced, therefore the relevant strategies ("annual basin-wide of long-term drought prevention") should be carried out [21]. Shi et al (2014) showed that the reservoir regulations had apparently altered the monthly and seasonal streamflow in the upper HRB. The decreasing trend of the annual streamflow was found, and human activities were proven to be the dominant driving factor behind the decreasing annual streamflow [22].…”
Section: Introductionmentioning
confidence: 99%